Comparative proteomic analysis of secretory proteins of Mycoplasma bovis and Mycoplasma mycoides subsp. mycoides investigates virulence and discovers important diagnostic biomarkers - Dawood, A.S.; Zhao, G.; He, Y.; Lu, D.; Wang, S.; Zhang, H.; Chen, Y.; Hu, C.; Chen, H.; Schieck, Elise G.; Guo, A. (MDPI, 2023)
The most important pathogenic Mycoplasma species in bovines are Mycoplasma bovis (M. bovis) and Mycoplasma mycoides subsp. mycoides (Mmm). Mmm causes contagious bovine pleuropneumonia (CBPP), which is a severe respiratory disease widespread in sub-Saharan Africa but eradicated in several countries, including China. M. bovis is an important cause of the bovine respiratory disease complex (BRD), characterized worldwide by pneumonia, arthritis, and mastitis. Secreted proteins of bacteria are generally considered virulence factors because they can act as toxins, adhesins, and virulent enzymes in infection. Therefore, this study performed a comparative proteomic analysis of the secreted proteins of M. bovis and Mmm in order to find some virulence-related factors as well as discover differential diagnostic biomarkers for these bovine mycoplasmas. The secretome was extracted from both species, and liquid chromatography-tandem mass spectrometry was used, which revealed 55 unique secreted proteins of M. bovis, 44 unique secreted proteins of Mmm, and 4 homologous proteins. In the M. bovis secretome, 19 proteins were predicted to be virulence factors, while 4 putative virulence factors were identified in the Mmm secretome. In addition, five unique secreted proteins of Mmm were expressed and purified, and their antigenicity was confirmed by Western blotting assay and indirect ELISA. Among them, Ts1133 and Ts0085 were verified as potential candidates for distinguishing Mmm infection from M. bovis infection.